Entrepreneurship Development in Nepal: A Case of ELAM - Bajracharya, Shilu Manandhar (PYC Nepal Journal of Management, 2011)
The importance of micro enterprise and entrepreneurship development in a poor country like Nepal cannot be overemphasized. Micro enterprises could seem easy tools to intervene for intervening to promote employment friendly strategies directed towards poverty reduction. However, developing entrepreneurship and micro enterprises is a daunting task in the state of vicious circle of poverty. In such a situation, ELAM programme can be effective in breaking the formidable circle, because the aim of ELAM interventions is to improve livelihoods condition by assisting the process of establishment of micro enterprises by poor communities. It has been so far successful in generating the sizeable number of potential clients, screening and enrolling the genuine clients into the programme by identifying potential clients with entrepreneurial traits, option and family support, potentials of mobilizing finance and credit, product market potentially, and creativeness.